A model for human-computer trust : a key contribution for leveraging trustful interactions - Sousa, Sónia (2016)
This article addresses trust in computer systems as a social phenomenon, which depends on the type of relationship that is established through the computer, or with other individuals. It starts by theoretically contextualizing trust, and then situates trust in the field of computer science. Then, describes the proposed model, which builds on what one perceives to be trustworthy and is influenced by a number of factors such as the history of participation and user's perceptions. It ends by situating the proposed model as a key contribution for leveraging trustful interactions and ends by proposing it used to serve as a complement to foster user's trust needs in what concerns Human-computer Iteration or Computermediated Interactions.